Preferensi Masyarakat dalam Membeli Jeruk di Kota Denpasar, Bali - SAVITRI, MADE AYU WINDA; YUSUF, RIA PUSPA; SUARDI, I DEWA PUTU OKA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2016)
Abstract Community Preference in Buying Oranges in Denpasar City, Bali Orange is one of the fruits that are often consumed by people. There are various types of local and import oranges in the market. In determining the choice or making decisions in product selection, every consumer are affected by preference. Preference is the tendency of consumer to choose one product rather than other products. Factors that are affecting consumer preferences in buying oranges are orange’s quality, social aspects, economic aspects, motivation, and continuity.The study conclude that the community preference in buying oranges in Denpasar city can be classified as a lot (7,105). The primary factor that has the greatest role is orange’s quality (19,05%), and social aspect (14,73%) has the lowest against the role of community preferences in buying oranges in Denpasar city. Secondary factor that have the greatest role ini community preferences in buying oranges are orange’s flavor (7,26%), and the lowest role of secondary factor is public knowledge regarding oranges (4,80%).
Keywords: community preference; factors of community preferences; oranges